PRMT5 Associates With the FOXP3 Homomer and When Disabled Enhances Targeted p185erbB2/neu Tumor Immunotherapy - Nagai, Yasuhiro; Ji, Mei Q.; Zhu, Fuxiang; Xiao, Yan; Tanaka, Yukinori; Kambayashi, Taku; Fujimoto, Shigeyoshi; Goldberg, Michael M.; Zhang, Hongtao; Li, Bin; Ohtani, Takuya; Greene, Mark I. (Frontiers in Immunology, 2019)
Regulatory T cells (Tregs) are a subpopulation of T cells that are specialized in suppressing immune responses. Here we show that the argininine methyl transferase protein PRMT5 can complex with FOXP3 transcription factors in Tregs. Mice with conditional knock out (cKO) of PRMT5 expression in Tregs develop severe scurfy-like autoimmunity. In these PRMT5 cKO mice, the spleen has reduced numbers of Tregs, but normal numbers of Tregs are found in the peripheral lymph nodes. These peripheral Tregs that lack PRMT5, however, display a limited suppressive function. Mass spectrometric analysis showed that FOXP3 can be di-methylated at positions R27, R51, and R146. A point mutation of Arginine (R) 51 to Lysine (K) led to defective suppressive functions in human CD4 T cells. Pharmacological inhibition of PRMT5 by DS-437 also reduced human Treg functions and inhibited the methylation of FOXP3. In addition, DS-437 significantly enhanced the anti-tumor effects of anti-erbB2/neu monoclonal antibody targeted therapy in Balb/c mice bearing CT26Her2 tumors by inhibiting Treg function and induction of tumor immunity. Controlling PRMT5 activity is a promising strategy for cancer therapy in situations where host immunity against tumors is attenuated in a FOXP3 dependent manner.